2015
DOI: 10.1007/s00535-015-1079-7
|View full text |Cite
|
Sign up to set email alerts
|

Excellent prognosis following endoscopic resection of patients with rectal neuroendocrine tumors despite the frequent presence of lymphovascular invasion

Abstract: This study showed an excellent long-term prognosis following ER of patients with rectal NETs, confirming that ER is a valid treatment option for small rectal NETs. The present study also revealed highly prevalent lymphovascular invasion even in minute rectal NETs; this observation raises a question regarding its significance as a risk factor for metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 41 publications
5
71
2
2
Order By: Relevance
“…Recently, immunohistochemical staining has been increasingly used for the accurate diagnosis of lymphovascular invasion [26][27][28]. Sekiguchi et al [28] retrospectively revealed that immunohistochemical staining identified almost half of the rectal NETs with lymphovascular invasion, while routine H-E staining identified only 1.2% in the same sample. Of note, although these patients did not undergo additional surgery, neither nodal nor distant metastasis occurred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, immunohistochemical staining has been increasingly used for the accurate diagnosis of lymphovascular invasion [26][27][28]. Sekiguchi et al [28] retrospectively revealed that immunohistochemical staining identified almost half of the rectal NETs with lymphovascular invasion, while routine H-E staining identified only 1.2% in the same sample. Of note, although these patients did not undergo additional surgery, neither nodal nor distant metastasis occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Although additional surgery should be considered in patients with rectal NETs harboring lymphovascular invasion, this approach needs further validation because the reported prevalence of lymphovascular invasion ranges widely from approximately 1% to a little less than 60% [14,26]. Recently, immunohistochemical staining has been increasingly used for the accurate diagnosis of lymphovascular invasion [26][27][28]. Sekiguchi et al [28] retrospectively revealed that immunohistochemical staining identified almost half of the rectal NETs with lymphovascular invasion, while routine H-E staining identified only 1.2% in the same sample.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al [16] reported that the 3-year survival rate was 100% among patients with RNETs ≤10 mm following ER. In addition, Sekiguchi et al [26] reported that 90 RNETs treated endoscopically were followed up without additional surgery, and no metastasis or recurrence was detected during the median follow-up period of 67.5 months despite the presence of LVI in nearly half of the lesions. These results showed an excellent prognosis following ER in patients with small RNETs.…”
Section: Clinical Outcomes Following Ermentioning
confidence: 99%
“…Sekiguchi et al [26] reported the frequent presence of LVI in small RNETs using immunohistochemical analysis (46.7%). Almost all the lesions were smaller than 10 mm in size, fulfilling the criteria for the application of ER.…”
Section: Lymphovascular Invasion In Small Rnetsmentioning
confidence: 99%
See 1 more Smart Citation